Free-to-total prostate-specific antigen ratio as a predictor of non-organ-confined prostate cancer (stage pT3). - Aus, G; Becker, C; Lilja, H; Khatami, A; Pihl, C; Hugosson, J (2003)
OBJECTIVE: To evaluate whether the free-to-total prostate-specific antigen (F/T-PSA) ratio can be used to differentiate between stage pT2 and pT3 prostate cancer. MATERIAL AND METHODS: A total of 176 consecutive patients from the Göteborg Screening Study (median T-PSA 4.2 ng/ml) who underwent radical prostatectomy (without neoadjuvant hormonal therapy) were included in the study. The pT stage was correlated with classical risk factors such as T-PSA and Gleason sum and the impact of the F/T-PSA ratio was evaluated. RESULTS: A total of 42/176 patients (23.9%) had stage pT3 prostate cancer. Patients with an F/T-PSA ratio in the lowest quartile (<10.7%) had extracapsular tumor growth in 46.5% of cases, compared to 16.7% for those with an F/T-PSA ratio >10.7% (p=0.0002). Patients with high-risk features (T-PSA >10 ng/ml or Gleason sum > or =7) had a high risk (54-60%) for stage pT3 prostate cancer. In low-risk patients, the subgroup with an F/T-PSA ratio <10.7% had a risk of 37.0%, compared to only 13.3% for those with a ratio of >10.7% (p=0.0092). CONCLUSIONS: In patients with low-risk early-stage prostate cancer, the F/T-PSA ratio provides statistically significant, independent and clinically relevant preoperative information about the risk of extracapsular tumor growth.